The effect of internship dimensions on the experience of De La Salle University Bachelor of science in accountancy students - Lu, Bernard Adrian Y. (Animo Repository, 2023)
Internships are crucial for college students, providing practical field exposure and skill refinement. The study examined the effect of internship dimensions of De La Salle University Bachelor of Science in Accountancy Students on their internship experience. Specifically, the study looked into the effect of Skill Variety, Task Identity, Task Significance, Task Autonomy, and feedback from the job on their internship experiences. The top four accounting firms were selected for insights based on intern participation. Data was collected from 95 respondents through a survey modeled on Hackman & Oldham's Job Diagnostic Survey. Statistical methods included regression, assumption tests, correlation, and descriptive analysis. The findings show that only task significance and feedback from the job significantly affect internship experience (p = .0298; p = .0034). However, partial slope estimates are relatively low (task significance = .1807; feedback from the job = 0.2792). This means a one-unit increase in task significance relates to a 0.1807 increase in perceived work meaningfulness. Similarly, a one-unit feedback increase yields a 0.2792 knowledge increase in work outcomes. This underscores that a positive internship experience BSA interns hinges on perceiving assigned tasks as impactful to others within and outside the firm and receiving substantial feedback on their contributions.